Health care costs associated with gestational diabetes mellitus among high-risk women - results from a randomised trial - Kolu Päivi; Raitanen Jani; Rissanen Pekka; Luoto Riitta (BMC, 2012)
Abstract Background The costs of gestational diabetes mellitus (GDM) screening have been frequently reported, but total GDM-related health care costs compared to the health care costs of women without GDM have not been reported. The aim of this study was to analyse GDM-related health care costs among women with an elevated risk of GDM. Methods The study was based on a cluster-randomised GDM prevention trial (N = 848) carried out at maternity clinics, combined with data from the Finnish Medical Birth Register and Care Registers for Social Welfare and Health Care. Costs of outpatient visits to primary and secondary care, cost of inpatient hospital care before and after delivery, the use of insulin, delivery costs and babies' stay in the neonatal intensive care unit were analysed. Women who developed GDM were compared to those who were not diagnosed with GDM. Results Total mean health care costs adjusted for age, body mass index and education were 25.1% higher among women diagnosed with GDM (€6,432 vs. €5,143, p < 0.001) than among women without GDM. The cost of inpatient visits was 44% higher and neonatal intensive care unit use was 49% higher in the GDM group than among women without GDM. The delivery costs were the largest single component in both groups. Conclusions A confirmed GDM diagnosis was associated with a significant increase in total health care costs. Effective lifestyle counselling by primary health care providers may offer a means of reducing the high costs of secondary care.